ESTIMATION OF GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE IN GENOTYPES OF MAIZE ( ANCE IN GENOTYPES OF MAIZE (Zea mays Zea mays L.) - DAN SINGH JAKHAR,; VIVEK KUMAR OJHA, RAJESH SINGH,; ANEESH KUMAR CHANDEL, CHANDAN KUMAR AND (The Bioscan, 2018)
The objectives of the study were to estimate the magnitude of genetic variability, heritability and genetic advance for yield and contributing characters of the thirty maize genotypes. These genotypes were evaluated during Kharif 2016 in a randomized block design with three replications. A high genotypic and phenotypic coefficient of variation was observed for plant height followed by ear height. Low, medium and high estimates of broad sense heritability were found in different plant characters under study. Highest heritability estimates were found in plant height (94.30%) followed by ear height (90.30%) and leaf width (85.60%). Plant height (41.74%) was exhibited highest genetic advance as per cent of mean followed by ear height (39.49%), leaf width (18.71%), cob length without husk (8.27%) and 100 seed weight (7.61%). Greater magnitude of broad sense heritability coupled with higher genetic advance in characters under study provided the evidence that these plant parameters were under the control of additive genetic effects.